Prospects for exploration of hydrogen fields in riftogene structures of platforms (the case of the Dnieper-Donets Aulacogene) - В. М. Шестопалов; О. Ю. Лукін; В.І. Старостенко; О. М. Пономаренко; T. О. Цветкова; І. Л. Колябіна; О. М. Макаренко; O. В. Усенко; О. Д. Рудь; A. Онопріенко; В. Ю. Саприкін; Р. Вардапелян (Геофизический журнал, 2021)
This paper shows the prospect to find industrial-scale hydrogen accumulations in riftogenic structures of platforms using the example of the Dnieper-Donets Aulacogene, located in the southern part of the East European Platform. Within the Dnieper-Donets Depression, geological and geophysical methods indicate a significant number of deep faults and ring structures of volcanogenic and explosive origin promising increased hydrogen content. Possible locations of the most propitious areas of hydrogen concentration are associated with faults in rift systems and their nearest margins, as well as with explosive and volcanogenic ring structures with signs of modern activation. At a fine-grained level, the prospectivity of the area is determined not only by the specified structural relationship, but also by the set of geophysical characteristics (thermal, seismic, gravity, electrical conductivity, magnetic) and the corresponding geological and hydrogeological parameters. Areas for further more detailed investigations within the Sribne and other ring structures, Southern Near-Edge Fault, Northern Near-Edge Fault were identified based on the data on geological and geophysical materials, satellite images, and field work. We defined high-priority and low-priority territories. Areas for initial investigations using satellite images, gas sampling (hydrogen, helium, methane, etc.), primary geophysical surveys (with evaluation of intermediate reservoirs and cap rocks) were identified. The primary results can be used to plan pilot shallow drilling and wells sampling. The areas for priority deeper drilling and sampling are selected by the sum of results obtained and data comparison. The paper presents the results obtained 30 km east of Kyiv as an example of field assessment of H2 degassing in a local depression. The results show that hydrogen concentrations at depths of 0.45 to 1.5 m are near zero outside the local depression. The maximum values of H2 concentration (up to 3300 ppm 1.5 m deep) are characteristic of the point inside the depression.